The Underlying Gendered Factors Influencing Access to and Utilization of Skilled Birth Attendance (Sba): A Case Study in Ghana - Ambrose, Naawa; Leonard, Baatiema; Kor, Jacob Aaworb-nang Maabobr; Sumah, Anthony Nwinkaara; Zwanikken, Prisca (Advances in Social Sciences Research Journal, 2022)
Maternal mortality continues to be a major public health concern in Ghana where women still die from preventable maternal deaths. Several factors contribute to the high maternal mortality in the country including delay in seeking skill birth attendance, sociocultural factors among others. Pursuance to the aforesaid, the study aimed at analyzing the role of gender in accessing skilled birth attendance in Ghana. A review of relevant literature was conducted to respond to the role of gender in accessing and utilizing skilled birth attendance. The search was conducted in Web of Science, Medline, PubMed, Academic Search Complete, and Cochrane database of systematic reviews including manual search of relevant literature in articles reference list. The 12 Centre for Evidence Based Management (CEBM) guidelines were used to assess the quality of the studies. The findings revealed a power play and a significant role of gender in accessing skilled birth attendance. Among the 10 studies included in this review, half of them were from northern Ghana whiles the other half in southern Ghana. Significant element discussed among the papers reviewed included male involvement, participation in decision making processes to seek skilled delivery and the effect of women social network. Men although appreciate the importance of skilled birth attendance, they are unable to provide the needed support to their partners during labour. The decision on the place of birth is mostly taken by the elderly women in the families. Gender indeed plays a significant role in determining women access and utilization of skilled birth attendance.